-36=s-63

Simple and best practice solution for -36=s-63 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -36=s-63 equation:


Simplifying
-36 = s + -63

Reorder the terms:
-36 = -63 + s

Solving
-36 = -63 + s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-1s' to each side of the equation.
-36 + -1s = -63 + s + -1s

Combine like terms: s + -1s = 0
-36 + -1s = -63 + 0
-36 + -1s = -63

Add '36' to each side of the equation.
-36 + 36 + -1s = -63 + 36

Combine like terms: -36 + 36 = 0
0 + -1s = -63 + 36
-1s = -63 + 36

Combine like terms: -63 + 36 = -27
-1s = -27

Divide each side by '-1'.
s = 27

Simplifying
s = 27

See similar equations:

| 3x+13=180 | | -9x-124=5x+44 | | 0.4+1.5=1.5+0.4 | | 3x-6+8x+4+50=180 | | 5x=4*20 | | 3=x-(-11) | | 8y=16*12 | | 4y=2*36 | | -48=33+a | | X+(x+4)+(x+8)+(x+12)+(x+16)+(x+20)=150 | | 5p-3=5(8p+6)-4(-5+9p) | | x^2-4x+1=10 | | 2x=18*5 | | m-51=-70 | | -112+x=40-7x | | 27m^2=3 | | 2-2-4= | | 1.5y=2.3 | | 4(x-y)+z=2x+z | | -2(x+2)-2x=5x-9 | | 3d=7*21 | | (x^2+4x-6)(x^2+6x-3)= | | 112+x=40-7x | | 0.5(3g-2)=g | | 3x+4y=35 | | d+25=b | | -3h+12-4h=-7h-16 | | -1=(x/4)-3 | | 2(-8+8x)+5x=-100 | | 3x+49=3 | | 3x+3y=20 | | 8c=7*16 |

Equations solver categories